Factors influencing special education teachers’ self-efficacy to provide transitional services for students with disabilities - Binammar, Sara; Alqahtani, Aljazi; Alnahdi, Ghaleb Hamad (Frontiers in Psychology, 2023)
This study examined factors that may influence the self-efficacy level of special education teachers in delivering transition services to students with disabilities. Five independent variables were examined: attitudes, preparation level, teaching experiences, academic degree level, and level of available resources. The current study sample comprised 231 intermediate and secondary special education teachers in the city of Riyadh, Saudi Arabia. The results showed that attitudes are the best predictor of teachers’ self-efficacy to provide transitional services for students with disabilities. Teacher preparation for transition services was the second most important variable that was positively associated with teachers’ self-efficacy.